B-lymphocytes as Targets for Therapy in Chronic Cold Agglutinin Disease - Berentsen, Sigbjorn; Ulvestad, Elling; Tjonnfjord, Geir E. (Cardiovascular & Haematological Disorders - Drug Targets, 2007)
Primary chronic cold agglutinin disease (CAD) is an autoimmune hemolytic anemia induced by cold reactive autoantibodies (cold agglutinins) against erythrocyte surface antigens. Corticosteroids or alkylating agents have been used in the treatment of CAD, but the results have been disappointing. The cold agglutinins in CAD patients are monoclonal immunoglobulins, usually of the IgMκ type encoded by the VH4-34 gene segment. Flowcytometric assessment of lymphocytes from bone marrow aspirates and immunohistochemical assessment of biopsy samples have revealed a monoclonal CD20+κ+ B lymphocyte population in 90% of the patients. These pathogenetic features have provided a basis for novel therapies in primary CAD. Infusions of rituximab, a chimeric human-murine anti-CD20 antibody known to be effective in B-cell lymphoma, produced partial response rates of approximately 50% and occasional complete responses. Median response duration, however, was only 11 months. Complement C3 and C4 depletion in many CAD patients, as well as Fcγ-RIIIa receptor polymorphism, have been proposed as explanations for the inconstant efficacy of rituximab therapy. In order to increase response rates and response duration, we are undertaking a phase 2 study of rituximab and fludarabine combination therapy. The preliminary results are encouraging, but further studies are required in order to allow firm conclusions.
Keywords: rituximab